On properties of modified degree six chordal rings network - Raja Maamor Shah, Raja Noor Farah Azura; Othman, Mohamed; Peng, Yee Hock; Selamat, Mohd. Hasan (Universiti Putra Malaysia Press, 2010)
Chordal rings are circulant graphs and have deserved significant attention in the last decade. Chordal rings were used to build interconnection networks for distributed and parallel systems. There are many of publications analyzing their networks properties. In this paper, we present the main properties of the latest method of chordal rings called Modified Chordal Rings Degree Six (CHRm6). The properties are connectivity, Hamiltonian cycle and asymmetry. We prove some lemmas and theorems for every property. All of these properties are useful for further works especially in developing a routing scheme.